Edukasi Dapat Meningkatkan Kualitas Hidup Pasien Yang Terdiagnosa Penyakit Jantung Koroner - Agus Purnama (Jurnal Kesehatan Indonesia, 2020)
Coronary Artery Diseases (CAD) is general term of bildup plaque at artery of cardiovascular which can lead to be Heart Attack. CAD can be prevented with health lifestyle and not consumption alcohol , avoid smoke and routine exercise. The purpose this research is to analysis influence education to quality of life with coronary artery diseass at RS X. The study design this research is quasy experiment with accidental sampling technique with the number of sample is 18 sample which devided to 2 group, the first group is control group and the second is intervention group. The sample at this research is patient with coronary artery diseases were treated at RS X. The data obtained from interviews using SF 36 questioners. Data analysis comprise univariate analysis and bivariate analysis. The result of this research that the highest incident of CAD is male (83,4%) with mean 55-56 years old. This research indicates with P value 0,019 with SD 16,488. Thus it can be concluded that education have the significant influence to quality of life with coronary artery disease at RS X. It is recommended that the study continue to be developed by further research in order to become better research.